Impact of land use changes on collapsed pipes development in the loess gully (Lublin Upland, East Poland) - Rodzik, Jan; Kołodyńska-Gawrysiak, Renata; Franczak, Łukasz; Zgłobicki, Wojciech; Poesen, Jean (Quaestiones Geographicae, 2024)
Subsurface erosion is a poorly recognized but important process for modelling and predicting gully erosion rates in loess areas. It is crucial to recognize the factors and mechanisms of soil piping and pipe collapse development. Our research is the first detailed description of the complex evolution of large collapsed pipes on the banks of a loess gully over 25 years (west part of Nałęczów Plateau, Lublin Upland). The objective of this study was to reconstruct the development of piping forms as a result of land use change. Detailed field observations and measurements after snowmelt and rainfall-runoff events formed the basis of the research. Sedimentary structures observed in the walls of recently collapsed pipes, filling up older piping forms, were studied. The human impact on the development of collapsed pipes has been significant. We found a multi-stage development of these forms with several cut and fill phases. An important factor influencing the formation and development of these forms was the change in land use (crop type and tillage direction). Farmers tried to reclaim collapsed pipes by filling them in with soil and incorporating them into the cropland. The resulting depressions had high infiltration rates resulting in a reactivation of soil piping processes. Increase of precipitation and the intensity of runoff caused the secondary stage of collapsed pipes development (with a volume ranging between 240 and 912 m3 per collapsed pipe). Changing runoff patterns as a result of human interventions decreased their activity, but caused the development of new (secondary) collapsed pipes.